Factors Determining Online And Offline Political Engagement In Malaysia - Murudi, Thanaraj (2023)
This study examines the factors determining civic voluntarism in political engagement in Malaysia. Focusing on civic voluntarism in influencing political engagement, this study applies Civic Voluntarism Model to elucidate the factors that influence the political engagement process. This study also acknowledges the dissatisfaction and fairness in politics and hence tests political dissatisfaction and perceived fairness in predicting citizens' political engagement factors.